Contribution of GalU to biofilm formation, motility, antibiotic and serum resistance, and pathogenicity of Salmonella Typhimurium - Guo, Lili; Dai, Huilin; Feng, Saixiang; Zhao, Yongda (Frontiers in Cellular and Infection Microbiology, 2023)
Salmonella Typhimurium is the important leading cause of foodborne illnesses in China, causing major epidemics and economic losses in recent years. GalU coding for uridine diphosphate-glucose pyrophosphorylase plays an important role in biosynthesis of the bacterial envelope. The study aimed to evaluate the role of galU gene in S. Typhimurium infection in chicken. The galU gene mutant was successfully constructed by red homologous recombination technology, and biological characteristics was studied. The results showed that galU mutant strain conformed to rough type, defected in biofilm formation, autoagglutination and motility ability, exhibited significantly more sensitivity to most antibiotics, serum and egg albumen, lower capacities of adhesion to DF-1 cell. In addition, the deficiency of the galU mutant drastically attenuated S. Typhimurium pathogenicity ability in chicken embryos (decreased by 100,000 times), BALB/c mice (decreased by 420 times) and chicks (decreased by 100 times). These findings imply that galU is an important virulence factor in S. Typhimurium. In conclusion, these results preliminarily indicated involvement of galU in the pathogenicity in S. Typhimurium, and this gene may be used as a target factor for the development of veterinary drugs for the disease, providing a theoretical basis for the prevention and control of the S. Typhimurium.